Prevention Practices from Water Borne Diseases within Households in the Bamendankwe Municipality-North West Cameroon (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: waterborne diseases; cholera; typhoid fever; dysentery; purification; chlorination; dehydration; diarrhea